1995
DOI: 10.1111/j.1365-2621.1995.tb01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic heating of Japanese white radish Rhaphanus sativus L.

Abstract: Summary Ohmic heating was applied to Japanese white radish, Rhaphanus sativus L. at 50 Hz‐10 kHz and 40 V cm−1 to examine the effects of frequency on the heat generation. Of the frequencies examined, 50 Hz gave the sharpest initial rise of temperature and the shortest time to raise the temperature at the mid‐part of radish to 80°C. The heating rates above 60°C were found to be almost the same and linear for all the frequencies. The pressurization (400 MPa, 25°C, for 10 min) of radish eliminated the sharp initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 17 publications
1
60
0
3
Order By: Relevance
“…This effect becomes more important with E increase from 40 to 100 V/cm. Imai et al [47] have found that OH behavior and impedance values of Japanese white radish depended from the frequency of electric field varied from 50 Hz to 10 kHz. At the constant voltage of 40 V/cm, the time necessary for heating the sample to the desired temperature was longer for higher frequencies of electric field.…”
Section: Principles Of Oh Treatmentmentioning
confidence: 99%
“…This effect becomes more important with E increase from 40 to 100 V/cm. Imai et al [47] have found that OH behavior and impedance values of Japanese white radish depended from the frequency of electric field varied from 50 Hz to 10 kHz. At the constant voltage of 40 V/cm, the time necessary for heating the sample to the desired temperature was longer for higher frequencies of electric field.…”
Section: Principles Of Oh Treatmentmentioning
confidence: 99%
“…Ohmic heating (also referred to as Joule heating, electroheating and electro conductive heating) is defined as a process wherein an electrical current (usually alternating) is passed through materials (Goullieux & Pain, 2005;Vicente, Castro, & Teixeira, 2006) and can be used to generate heat within the product (Imai, Uemura, Ishida, Yoshizaki, & Noguchi, 1995). The heating occurs in the form of internal energy transformation (from electric to thermal which is due to Joule effect) within the material (Sastry & Barach, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…To prevent undesirable electrochemical reactions between electrodes and solid or viscous liquid products, increasing the frequency or changing the waveform of alternating current has been suggested (10). There have been some efforts to clarify the impact of frequency and waveform of alternating current on ohmic heating rates of solid or semisolid foods (11)(12)(13)(14)(15). However, there has been no comprehensive research on the effects of frequency on electrode corrosion, electrical conductivity and microbial inactivation in solid-liquid food mixtures.…”
mentioning
confidence: 99%